Treatment of hiccup by vagal maneuvers - Petroianu, Georg (Journal of the history of the neurosciences, 2015)
A multitude of nonpharmacological interventions to terminate hiccup belong to the public-domain hiccup “mythology” or have been described in the medical literature as case reports. While usually effective in terminating bouts of acute hiccup, they are mostly ineffective in cases of hiccupping that have been present for an extended period. The common denominator of most of these therapeutic maneuvers (some also used to terminate paroxysmal supraventricular tachycardia) is their ability to directly or indirectly increase efferent vagal activity. Among the best known “vagal maneuvers” are the oculo-cardiac reflex (Dagnini-Aschner), the carotid sinus massage, the Valsalva maneuver, stimulation of the ear/auditory canal, ice ingestion, and induction of emesis. This short report provides an overview on hiccups and attempts to identify the lesser known personalities who pioneered its treatment by vagal maneuvers. The recent introduction of electrical vagus nerve stimulation for therapy-resistant hiccup is the ultimate compliment to these pioneers.